Drought response strategies of Arbequina, Arbosana and Koroneiki olive cultivars revealed by ring growth, wood anatomy and δ¹³C dynamics - Portarena, Silvia; Saurer, Matthias; Brugnoli, Enrico; Farinelli, Daniela; Cherubini, Paolo (Frontiers in Plant Science, 2025)
The olive tree (Olea europaea L.), a key crop in Mediterranean climates, is increasingly affected by climate variability. Over the last several decades, the Umbria region of central Italy, with its long-standing olive-growing tradition, has experienced a rise in extreme summer droughts, severely impacting water availability. This makes it an ideal case study for investigating olive tree responses to climatic stress. In this study, we examined the adaptive strategies of three economically important cultivars – Arbequina, Arbosana, and Koroneiki – grown as mature trees (7 years old) between 2020 and 2023. We combined dendrochronological techniques, wood anatomical analyses, and intra-seasonal δ¹³C profiling to assess growth dynamics, structural adjustments, and eco-physiological responses across four growing seasons. Our results revealed distinct cultivar-specific strategies in response to climate variation. In Arbequina and Arbosana, δ¹³C values showed significant correlations with current-year spring and summer climate conditions, as well as with conditions during the preceding winter, reflecting a more isohydric behavior. In contrast, Koroneiki exhibited a more anisohydric strategy: its δ¹³C values were primarily influenced by precipitation from the previous winter, indicating a reliance on stored carbon reserves to support early-season growth. Wood anatomical traits further supported these differences. Koroneiki exhibited higher vessel density and a greater proportion of lumen area, traits that enhance water transport efficiency. It also achieved the highest stem basal area and fruit production among the three cultivars, reaching 10.2 kg/tree in 2023. These characteristics highlight Koroneiki’s potential as a drought-resilient cultivar suited for future orchard designs in Mediterranean regions increasingly affected by heat and water stress.